Pengaruh Literasi Keuangan, Pendidikan Keuangan Di Keluarga Dan Kontrol Diri Terhadap Manajemen Keuangan Pribadi Remaja - Agassi Dwi Putra; Muhammad Mansur; Budi Wahono (UNIVERSITAS ISLAM MALANG, 2023)
Abstract This study aims to determine and analyze the effect financial literacy, financial education in the family, and self-control over personal financial management. The population in this study are Malang Islamic University students. The data collection method in this study used a questionnaire with a sample of 85 respondents. The independent variable in this study is the financial literacy, financial education in the family, and self-control and the dependent variable is the financial management. The analytical method used in this study is multiple linear regression analysis and processed using SPSS 26. The results of this study simultaneously show that the financial literacy, financial education in the family, and self-control has a positive effect on financial management. Partially, financial literacy, financial education in the family, and self-control have a positive effect on financial literacy. Keywords: financial literacy financial education in the family, self-control and financial management.